Musculoskeletal modeling of optimal soccer kick to evaluate selected muscles function - Hajlotfalian, M.; Honarvar, M. H.; Shamsehkohan, P. (Journal of Advanced Sport Technology, 2019)
Electromyography is a common method to calculate muscle`s function. But it has some limits. Musculoskeletal modeling is an indirect method to consider muscle`s function, by using kinematic and kinetic characteristics of subject`s movement. The purpose of this study was to investigate and compare some selected muscles of prefer leg during performing two different kick patterns which consist of subject kick pattern and optimal kick pattern which created from same subjects by mechanical model. OpenSim 3.2 platform and Computed Muscle Control (CMC) tool were used to simulate muscles function. After selecting a 3D model of leg which consists of six degree of freedom and nine vital muscles, biomechanical parameters of two kick patterns, entered into model and run. Afterwards data were normalized and filtered. Paired sample t- test was used to analyze data. After compared two kick patterns, there were significant difference in contraction force of iliopsoas, biceps femoris long head and biceps femoris short head, rectus femoris, vastus lateralis and tibialis anterior. In addition, vastus lateralis, rectus femoris, iliopsoas and tibialis anterior were must important muscles in forward swing phase of two patterns of soccer kick. Also, iliopsoas and quadriceps were more active in subjects and optimal pattern, respectively. The results revealed that, the interaction of muscles stimulation, joints motion and more activity of quadriceps, were main factors to increase the speed of optimal kick. Results from the musculoskeletal model, had a great similarity with the results of previous experimental studies. Incidentally this apparatus can simulate muscles activity, with high precision and considering the advantages of that, this method can be used in sports biomechanics and medicine research.